The Effect of Work Motivation, Work Environment, and Job Insecurity on Turnover Intention: The Role of Job Satisfaction as a Mediator in Denpasar's Workforce Development - Putri, Kadek Winda Pardana; Maradona, Agus Fredy (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to test the effect of work motivation effect on Turnover Intention, to test the effect of work environment effect on Turnover Intention, to test the effect of Job Insecurity effect on Turnover Intention, to test the effect of work motivation effect on job satisfaction, to test the effect of work environment effect on job satisfaction, to test the effect of Job, to test the effect of work motivation effect on Turnover Intention mediated by job satisfaction, to test the effect of work environment effect on Turnover Intention mediated by job satisfaction, to test the effect of Job Insecurity effect on Turnover Intention mediated by Job Satisfaction. The Data to be used in this study is quantitative data. The results showed that work motivation has a negative and significant effect on turnover intention. The work environment has a negative and significant effect on turnover intention. Job insecurity has a positive and significant effect on turnover intention. Work motivation has a positive and significant effect on job satisfaction. The work environment has a positive and significant effect on job satisfaction. Job insecurity has a positive and significant effect on job satisfaction. Job satisfaction has a negative and significant effect on turnover intention. Job satisfaction can be an intervening variable on the effect of work motivation on turnover intention. Job satisfaction can be an intervening variable in the influence of the work environment on turnover intention. Job insecurity can be an intervening variable in the influence of the work environment on turnover intention.